SECURING INDONESIA’S EXTRACTIVE INDUSTRIES THROUGH SOCIAL LICENSE TO OPERATE - Imam Mulyana (Faculty of Law Universitas Padjadjaran, 2021)
Public participation is one of the important factors in the extractive industry, especially to ensure that the development of new mining projects can begin successfully. Social License to Operate (SLO) is a contemporary concept that rapidly develops and is widely known as a method for building relationships between mining companies and the communities surrounding the mining project. This article attempts to introduce the concept of SLO and provide an initial overview of the implementation of SLO in the extractive industry in Indonesia. In addition, this article also examines the relationship between SLO and another similar concept, namely Environmental Impact Analysis (EIA). This article finds that although SLO and IEA have differences, the similarities between the two concepts could potentially be unified to cope with the shortcomings mutually. After analysing the implementation of SLO in several mining projects in Indonesia and considering the issuance of Law no. 11 of 2020 concerning Job Creation, this article argues that the existence of SLO could be utilized as an alternative method to strengthen the relationship between community and mining companies, improve the quality of participation, and reduce community resistance to the development of extractive industry projects in Indonesia.